Thyroid dysfunction in India: what is different - Singh, S. K.; Singh, Rina; Singh, Santosh Kumar; Pandey, Arun Kumar; Jaiswal, Sarika; Rai, Pradeep Kumar (International Journal of Advances in Medicine, 2024)
Thyroid dysfunction (TD) is a common endocrine condition worldwide. Thyroid hormone is essential for growth, development, and energy metabolism. TD if left untreated leads to various serious health consequences. Various risk factors for the development of TD are iodine deficiency, ageing, genetic susceptibility, smoking status, ethnicity, and endocrine disruptors. Indians are at high risk for the development of TD as compared to Caucasians. Indian thyroid patients differ than Caucasians in many aspects such as higher prevalence of congenital hypothyroidism and other TD, higher rate of progression of subclinical hypothyroidism (SCH) to overt hypothyroidism (OH), and lower prevalence of thyroid associated ophthalmopathy (TAO). In this article, we tried to summarize the current evidences regarding environmental and biological factors that place Indians at high risk of TD as compared to other ethnic groups. High prevalence and different characteristics of Indian TD call for investigation into cause of increased susceptibility and way to prevent TD at individual and population levels.